Pengaruh Kebijakan Dividen, Kebijakan Utang, dan Pertumbuhan Perusahaan terhadap Harga Saham - Nurochman, Ali; Hunein, Hamida (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to provide empirical evidence of the effect of Dividend Policy, Debt Policy, and Company Growth on Stock Prices. This study uses a quantitative approach and the data used is secondary data. The population in this study were Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The method in determining the sample uses purposive sampling. Obtained a sample of 25 companies with a period of 5 years. The data analysis technique used is multiple linear regression analysis. The F test results show that simultaneously Dividend Policy, Debt Policy, and Company Growth have a significant effect on Stock Prices. The t test results show that the Dividend Policy partially has a positive effect on stock prices, but the Debt Policy partially has no significant effect and Company Growth partially has no significant effect.